Avaliação elétrica e eletroquímica de ferritas de cálcio do tipo brownmillerita obtidas pela rota sol-gel protéica e por reação de estado sólido usando conchas de molusco - Lima, Chrystian Gregório Medeiros de (2022)
The environmental problem has been driving research around the world with a focus, mainly, on new energy sources. Technologies in the development of new materials for application in this area have been fundamental to make the use of these energy sources increasingly accessible in our daily lives. Fuel cells is an example of this kind of new technology, where we have an electrochemical device that converts chemical energy from reactions into electrical energy. Thermoelectrics also fall into this category, and are devices that, through a temperature gradient between two junctions, can generate electrical energy. Brownmillerita (Ca2Fe2O5) calcium ferrite ceramics were prepared by two distinct routes, namely, by a sol-gel protein synthesis using commercial unflavored gelatin, and by a solid-state reaction method, using mollusk shells. In addition, samples doped with cobalt, Ca2Fe2-xCoxO5 (with x = 0, 2, 4, 6 and 8%) were prepared for the study of the oxygen evolution reaction (OER) and electrode impedance in a symmetric cell, using ceria doped with gadolinium (CGO) as an electrolyte. XRD analyzes confirmed single-phase brownmillerita calcium ferrites in both production routes. SEM-EDS analysis of sintered Ca2Fe2O5 ceramics revealed larger grain sizes for samples prepared using the solid state reaction. All samples had a p-type conduction mechanism, with the highest power factor of ~ 2 μWm-1 K-2 at 450 °C observed for samples obtained by means of the solid-state reaction. The cobalt-doped samples showed XRD patterns without secondary phase. The results obtained in the OER indicated competitive values in terms of the electrochemical kinetics of the material as a catalyst when compared to the literature, where a sample with 2% cobalt showed a lower Tafel slope, of 37.5mV.dec-1, compared to the other samples. Electrochemical impedance spectroscopy also showed interesting values in terms of capacitance and resistance, associated with the relaxation frequency, during the OER steps. In the study of calcium ferrite as an electrode, it was observed a good adhesion to the substrate (CGO electrolyte), having a porous and well percolated microstructure, with slightly smaller grain sizes in the sample with cobalt doping. In addition, it can be observed from the low and high frequency processes, in the impedance, the influence of cobalt doping. The activation energy for the polarization resistance term, for example, obtained for Ca2Fe1.2Co0.8O5 was slightly lower, 1.19 eV, while for the pure sample it was 1.27eV. Therefore, the results obtained showed that the proposed synthesis routes can be successfully used in the preparation of single-phase materials of the brownmillerite type, where satisfactory results were obtained for several electrochemical applications, such as electrochemical catalyst, electrode for SOFC and thermoelectric.